I, Durga Khote : an autobiography - Khoṭe, Durgā (Oxford University Press, 2006)
I, Durga Khote is the account of the life and work of an actress who entered the world of Indian films when women from respectable families were still forbidden to do so. Durga Khote, one of the most respected actresses of Hindi and Marathi cinema, gives a lively, and crisp account of the bright and the dark strands of her life with the skill of a born storyteller.